INA529: Environmental Psychology / College of Built Environment - UiTM, College of Built Environment (2023)
The course focuses on the study of human behavior with regard to the environment. Basic understanding on the components of the human behavior such as perception, cognition and attitude is being introduced. Factors that affect the human behavior such as ambient, personal apace, territoriality, stress and etc. Is being discussed and in the later part specific type of spaces are being studied with regard to human behavior.